Transient and steady-state analysis of queueing systems with catastrophes and impatient customers. (1st January 2014) - Krishna Kumar, B.; Anantha Lakshmi, S.R.; Anbarasu, S.; Pavai Madheswari, S.
Sudhesh (2010) has discussed the transient probabilities for queueing systems subject to catastrophic failures and impatience of customers. However, it contains some errors concerning the terminology and the final forms of the transient probabilities of the system size. In this paper, we correct the errors and obtain the correct results in the work carried out by Sudhesh. In addition, the steady state system size probabilities and performance measures are provided. Finally, two special cases are deduced from the more general queueing model under study.